Validation of sampling, isolation and identification technique for Phytophthora infestans: Species and mating type - Ade Mahendra Sutejo; Wibowo, Arif; Joko, Tri; Widiastuti, Ani (Agriculture and Natural Resources, 2026)
Importance of the work: Sample damage and misleading Phytophthora infestans identification are frequent, which could be addressed by the development of suitable validation sampling, isolation and identification techniques. Objectives: To compare several methods for the sampling, isolation and identification of P. infestans using molecular and conventional approaches. Materials and Methods: Infected potato leaves were used as the source of isolates and for culturing. Whatman paper, DNA extraction kit and V-8 agar medium were used for sampling, DNA isolation and culturing, respectively. Polymerase chain reactionrestriction fragment length polymorphism (PCR-RFLP) used specific marker and restriction enzymes for species and mating type identification. Results: The Whatman paper could be an alternative for DNA sampling due to being more affordable, available and simpler to use than a Flinders Technology Agreement Card. Marker O8-1F/2R showed high sensitivity for species identification among the four markers tested. A 245 bp of PCR product followed by sequencing, blasting and constructing a phylogenetic tree showed high sensitivity in the levels of species, genus and class. The combination pairing method, molecular marker PCR-RFLP (W16-1F/ 2R fb. BsuRI) and sequencing constituted the best technique for mating type identification, while the SmaI enzyme could be an alternative. Main finding: Whatman paper could solve the long distance sampling issue. Marker O-1F/2R fb. sequencing was the most accurate marker for species identification, whereas a combination of W16-1F/2R fb. BsuRI or SmaI, sequencing and a pairing test produced better results in mating type determination.